Büntetőjogi joggyakorlat a Miskolci Királyi Törvényszéken 1944-ben - Lehotay, Veronika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
This essay focuses on criminal suits in the Court of Justice in Miskolc (county capital of Borsod-Abaúj-Zemplén in Hungary) during World War II. It analyses the content and the number of different cases. The number of cases was about ‘slandering the Hungarian state and nation', dissemination of false news, and incitement to Hungarian armed forces. The study reveals that very few numbers of cases related to the Anti-Jewish laws in county Borsod, which was rather characteristic in the countryside out of Budapest. For example, in 1943 and 1944, only four trials based on race defilement.